2016
DOI: 10.18869/acadpub.hms.22.4.307
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Physical Activity on Serum Homocysteine Levels in Obese and Overweight Women

Abstract: Aims: Recently, homocysteine has been noticed as the major pathogenesis factor of the cardiovascular diseases. The aim of the study was to investigate the effects of physical activities on the serum homocysteine levels, as well as other cardiovascular risk factors in either obese or overweight women. Materials & Methods: In the controlled pretest-posttest semi-experimental study, 18 women referred to the Alzahra sport complexes in districts 3 and 4 of Tehran were studied in 2015. The subjects were selected via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Woolf et al, (2017) demonstrated that physical exercise increases folate concentration in blood which lowers the homocysteine in blood. Soori at al., (2016) revealed that ten week physical exercise reduces concentration of homocysteine in blood and reduces risk for cardiovascular disease in overweight women. These reports are consistent with our findings that a major role of physical activity in lowering the homocysteine concentration in blood by which it reduces the risk of cardiovascular and neurological disease.…”
Section: Resultsmentioning
confidence: 99%
“…Woolf et al, (2017) demonstrated that physical exercise increases folate concentration in blood which lowers the homocysteine in blood. Soori at al., (2016) revealed that ten week physical exercise reduces concentration of homocysteine in blood and reduces risk for cardiovascular disease in overweight women. These reports are consistent with our findings that a major role of physical activity in lowering the homocysteine concentration in blood by which it reduces the risk of cardiovascular and neurological disease.…”
Section: Resultsmentioning
confidence: 99%